Historical Analysis of Islamic Philosophical Thought According to Imam Al-Ghazali - Sugih Nugraha; Neneng Suwerma; Didik Himmawan (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2024)
Imam Al-Ghazali is a major figure in the history of Islamic thought, famous for his controversial works such as "The Incoherence of the Philosophers" (Tahafut al-Falasifah) and "The Aims of the Philosophers" (Maqasid al-Falasifah), as well as several other works which is significant. His critique of rationalist philosophy highlights that reason is insufficient to understand God; spiritual experience is necessary. Al-Ghazali integrated philosophy and theology, emphasizing that the development of reason must be accompanied by divine revelation. His work strengthened the theological foundations of Islam and made major contributions to intellectual and spiritual thought in the Islamic world. This research focuses on Al-Ghazali's four main thoughts, although he had other views in different contexts that are not discussed in this paper. This research uses the library research research method. The main advantage of this method is wide access to various existing sources of information without having to collect primary data, making it more efficient in time and costs. The results of this research, namely Al-Ghazali's thoughts, provide in-depth insight into the relationship between philosophy and religion in Islam, and have a significant impact on the development of intellectual and spiritual thought in the Islamic world.